Revit and Unreal Engine: Real-Life Architectural Visualizations. - Bryant, Shaun (linkedin.com, 2020)
Bring your Revit models to life with architectural visualization. Learn how to use Unreal Engine to transform your Revit designs into highly realistic images and videos.